ANALISIS RASIO LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN KIMIA FARMA PADA PT. KIMIA FARMA Tbk - Oktaviani, Dela; Febriyanto, Vino (Journal of Information System, Applied, Management, Accounting and Research, 2025)
A company's financial performance is a description of the activities carried out to achieve business goals at a certain time and as reference material to determine the extent to which the company has achieved its achievement targets in order to maintain its stability. To find out the company's financial performance, you can look at its financial reports. The type of research used is descriptive qualitative. The type of data used is the company's annual financial report data for 2019-2023. The population and sample in this research are the company's financial reports at PT. Kimia Farma Tbk Period 2019-2023. The data collection techniques used are documentation and observation. The data obtained is then analyzed using liquidity ratios (current ratio and quick ratio), profitability ratios (Net Profit Margin, Return on Assets, and Return on Equity). And solvency ratios (Debt to Asset Ratio and Debt to Equity Ratio). The results of this research indicate that financial performance as measured by the liquidity ratio can be considered not good, measured by the profitability ratio is considered not good, and measured by the solvency ratio which is considered not good.